SECONDARY ABDOMINAL PREGNANCY IN A EWE - KUMAR, R ANIL; SRINIVASAN, P; KRISHNAKUMAR, S (The Indian Journal of Animal Reproduction, 2022)
A case of secondary abdominal pregnancy in ewe was reported. The dead fetus was removed surgically fromthe abdominal cavity. Uterine rupture was attributed to be the cause of the abdominal pregnancy.
Keywords: Sheep; Secondary abdominal pregnancy; uterine rupture